Dangerous dining - Waring, Rob.; National Geographic Society (U.S.) (Boston, Mass. : Heinle, Cengage Learning, 2009)
The puffer fish is a famous type of fish in Japan. If it's prepared properly, it's a safe and delicious meal. If it's not, it can kill those who eat it. How do chefs prepare the fish correctly? What
Footprint reading library with video from National Geographic--Cover
language bookfair2015
Keywords: Poisonous fishes -- Juvenile literature. -- Japan; Fish as food -- Japan; Reading (Elementary)